Molecular epidemiology of Neisseria gonorrhoeae isolates in Russia, 2015–2023: current trends and forecasting - Kandinov, Ilya; Shaskolskiy, Boris; Kravtsov, Dmitry; Larkin, Anatoliy; Kubanov, Alexei; Shpilevaya, Marina; Shagabieva, Julia; Nosov, Nikita; Gryadunov, Dmitry (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe emergence of multidrug resistance in N. gonorrhoeae is a serious global problem, and gonorrhea may soon become an incurable disease. The aim of the study was to characterize the N. gonorrhoeae population in Russia from 2015 to 2023 and predict the potential spread of the most concerning clones.MethodsA total of 996 N. gonorrhoeae isolates were examined during the analyzed period. Ceftriaxone and azithromycin susceptibility testing were performed using the agar dilution method. Microarray-based assays and sequencing were employed to identify the genotypes and genetic markers of antimicrobial resistance.ResultsNo ceftriaxone-resistant isolates were found in Russia, however, the number of isolates with reduced susceptibility to ceftriaxone has increased to 22.6% in recent years. Since 2020, approximately 12.5% of isolates have exhibited resistance to azithromycin annually. Two clusters of isolates pose a particular threat to Russia: NG-MAST G2212, linked to MLST 1901/1902, carries a mosaic structure in the penA gene; G12302, linked to MLST 9363, contains mosaic alleles in the mtrR and mtrD genes. Additionally, two new high-risk genogroups were characterized: G18898 and G16206. Both are associated with MLST 10314 and harbor mosaic variants of penA or mtrR/mtrD. Analysis of time series data suggests that isolates with mosaic alleles are unlikely to be eradicated from the population in the near future, potentially worsening the epidemiological situation of gonorrhea in Russia.ConclusionsThe native genetic strains of N. gonorrhoeae in Russia, which are susceptible to cephalosporins and macrolides, are being progressively replaced by globally dominant lineages. To further characterize this epidemiologic shift, ongoing surveillance strategies using molecular epidemiology and the identification of genetic markers will be crucial in curbing the growth and spread of N. gonorrhoeae resistance. Such efforts are vital in ensuring the availability of effective treatments for gonococcal infection.